Use Of Final Income Tax Incentives In MSME Tax Reporting During The Covid-19 Pandemic - Pradata, Bramastyasa Gilang; Chairunnisa, Tasya (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The Covid -19 virus outbreak created impact bad to sector world economy including Indonesia. Micro, Small and Medium Enterprises (MSMEs) are one of them affected sectors pandemic This. Various effort has carried out by the government For build return Indonesia's economy so that it always walk with well, one its policy issued via PMK No. 44/PMK.03/2020 concerning incentive taxation or giving facility subtraction even liberation payment taxes, incl Final Income Tax for MSMEs that have Lots benefit towards MSME actors Alone. Research purposes This is For know how to do it submission and reporting incentive FINAL PPh DTP for MSMEs is appropriate with PMK No. 44/PMK.03/2020 and PP 23 of 2018 What just benefits obtained top MSME players utilization incentive FINAL PPh DTP. Result of study This Still many MSMEs do not understand and use incentive Final Income Tax during the Covid 19 pandemic against reporting MSME tax due to limitations knowledge and still must done guidance and outreach by the government, because MSMEs provide contribution yan big in development economy in Indonesia.